Effects of integrated sound word method in teaching early reading to ESL preschoolers / Tham Kwee Eng - Tham , Kwee Eng (2020)
This research study serves to examine effects of Integrated Sound Word Method in teaching early reading to ESL preschoolers. Its purpose is to fill the gaps of the English language deficiency among Malaysian students where strong influence of mother tongue language, students’ social and emotional state as well as lack of conducive learning environment affect the Second Language acquisition. A quasi-experimental research was conducted in two preschools in the district of Kuala Lumpur. A purposive sampling method is chosen for this study to identify 60 government preschoolers who are weak in the English language proficiency. The preschoolers are equally divided into a control group and an intervention group. The findings have shown the Integrated Sound Word Method elicited significant effects in reducing the numbers of early reading errors, improving the early English reading proficiency and retaining the early reading knowledge among ESL preschoolers. This study able to provide an alternative for teaching early reading to ESL in preschools, however it is hoped that future researchers could further explore the Integrated Sound Word Method in teaching the English language in other fields. Acknowledging the importance of the English language in the 21st century, educators should well equip with effective teaching instructions to prepare students face challenges in the world without boundaries.